Propagación in vitro y actividad antimicrobiana de extractos de callos obtenidos de especies del género Rubus spp. - Tapia Pérez, Alejandra (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
In vitro tests have determined that the best treatment of sepsis was using 10% bleach for all materials by varying the time of 10 min for Raspberry and 20 min for Waxy and Hairy, a survival rate of 67, 70 and 55%, respectively. In Micropropagation with BA results showed a bound material effect because while the Raspberry at a concentration of 2.0 mgL-1 was obtained 8.41 buds, Waxy and Hairy blackberries to 8.36 and 6.59 shoots, respectively was obtained, but to supplement the culture medium containing amino acids, and Hairy Cerosa blackberries sprouts obtained higher , being 4.10 and 3.71brotes explant. In step with AIA elongation, concentration 0.1 mgL-1 had the highest effect on stem length in the three species, with the measures obtained 6.06 , 6.1 and 3.42 cm , while in the rooting stage the best treatment AIB was 0.5 mgL-1 to achieve a root length of 6.79, 7.20 and 7.00 cm ( respective data Raspberry, waxy and Hairy ) and AIA was demonstrated that species perform better in the absence of it, since it was obtained more length of their roots being 2.88, 3.44 and 1.92 cm, respectively. In the generation of callus induction was favored 1 mgL-1 of 2,4-D in the three species , giving percentages of up to 100% induction and percentages friable callus 83.3% as was the case of the waxy. In micropropagation species differed with the greater growth in different treatments, in the case of Raspberry and Waxy medium supplemented with NAA and BA had the highest PF calluses between 17 and 20 days ( 3.57 and 3.37 gr. ) hairy in medium supplemented with IAA, IBA , NAA and BA was the most favorable to get a PF of 2.92 gr. in their callus on day 19.

Las pruebas in vitro determinaron que el mejor tratamiento de asepsia fue utilizando cloro al 10% para todos los materiales variando el tiempo de 10 min para Frambuesa y 20 min para Cerosa y Vellosa; con un porcentaje de sobrevivencia de 67, 70 y 55%, respectivamente. En la Micropropagación con BA los resultados mostraron un efecto ligado al material, ya que mientras que la Frambuesa a concentración de 2.0 mgL-1 obtuvo 8.41 brotes, las zarzamoras Cerosa y Vellosa a se obtuvo 8.36 y 6.59 brotes, respectivamente; pero al suplementar el medio de cultivo con aminoácidos, las zarzamoras Cerosa y Vellosa obtuvieron mayor número de brotes, siendo de 4.10 y 3.71brotes por explante. En la etapa de alargamiento con AIA, la concentración 0.1 mgL-1 obtuvo el mayor efecto en la longitud de tallo en las tres especies, siendo las medidas obtenidas de 6.06, 6.1 y 3.42 cm; mientras que en la etapa de enraizamiento el mejor tratamiento con AIB fue 0.5 mgL-1 al lograr una longitud de raíz de 6.79, 7.20 y 7.00 cm (datos respectivos a Frambuesa, Cerosa y Vellosa) y con AIA se demostraron que las especies actúan mejor en ausencia de ella, puesto que se obtuvieron mayor longitud de en sus raíces siendo de 2.88, 3.44 y 1.92 cm, respectivamente. En la generación de callo, la inducción fue favorecida a 1 mgL-1 de 2,4-D en las tres especies, obteniendo porcentajes de hasta el 100% de inducción y porcentajes de 83.3% de callos friables como fue el caso de la Cerosa.
Instituto de Investigaciones Agropecuarias y Forestales. Facultad de Biología. Facultad de Medicina Veterinaria y Zootecnia. Facultad de Agrobiología. Facultad de Químico Farmacobiología. Programa Institucional de Maestría en Ciencias Biológicas
Keywords: info:eu-repo/classification/cti/6; FAPJ-M-2014-0291; Compuestos; Polifenólicos; Antimicrobiana; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2049